2012
DOI: 10.1091/mbc.e12-05-0343
|View full text |Cite
|
Sign up to set email alerts
|

Sec1/Munc18 protein Vps33 binds to SNARE domains and the quaternary SNARE complex

Abstract: Vps33, a member of the Sec1/Munc18 family of soluble N-ethylmaleimide–sensitive factor attachment protein receptor (SNARE) chaperones, is a subunit of the homotypic fusion and protein sorting and class C core vacuole/endosome tethering complexes and essential for endolysosomal transport. In this study, Vps33 interactions with SNARE proteins are investigated using genetic and biochemical approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
133
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(148 citation statements)
references
References 56 publications
12
133
3
Order By: Relevance
“…Our analyses on the Vam3 interaction of HOPS differ in some small but critical points from previous work on Vps33 (13,14). Although we observe similar interactions of HOPS with Ykt6 and assembled SNAREs (Ref.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Our analyses on the Vam3 interaction of HOPS differ in some small but critical points from previous work on Vps33 (13,14). Although we observe similar interactions of HOPS with Ykt6 and assembled SNAREs (Ref.…”
Section: Discussioncontrasting
confidence: 82%
“…Segment of Vam3-Recent work of Merz and co-workers (13,21) nicely demonstrated the interaction of isolated Vps33 with vacuolar SNAREs and suggested that Vps33 facilitates the assembly of SNAREs. Because we would like to correlate the binding ability with fusion activity, we focused on the entire HOPS complex instead.…”
Section: Identification Of the H Abc Domain As The Main Hops Bindingmentioning
confidence: 94%
See 1 more Smart Citation
“…Order-of-addition experiments show that Munc18-2 accelerates the formation cdV8-resistant SNARE complexes, therefore supporting a role of Munc18-2 in proof-reading trans-SNARE complexes (52,(55)(56)(57). Additionally, our data also suggest that Munc18-2 facilitates SNAREpin zippering similarly to other SM proteins (43,54,(58)(59)(60)(61)(62)(63). Thus, although the GPI anchor may be less effective than the transmembrane domain in transducing the energy of SNARE assembly to drive membrane fusion, the increased number of assembled STX11-GPI SNARE complexes generated in the presence of Munc18-2 likely cooperate, giving rise to a higher energetically favorable state that could be sufficient to destabilize the phospholipid bilayers and result in complete membrane fusion.…”
Section: Discussionsupporting
confidence: 75%
“…Vps33, one of the HOPS subunits, is the vacuolar SM (Sec1/ mUNC-18 family) protein. HOPS has direct affinity for vacuolar SNAREs (14)(15)(16), and helps to catalyze SNARE complex assembly and the subsequent fusion (17).…”
mentioning
confidence: 99%